A Literature Survey on Different Techniques Based Recommendation Systems (International Journal of Food and Nutritional Sciences, 2021)
ABSTRACT: From the past decade, there are many recommended system are being used for determining various problem in different field like entertainment, social media and e-commerce. Recommendation systems are like intelligent filters which process a huge amount of information with respect to the preferences of the user and then provide suggestions to them in the form of recommendations such as recommending movies to watch, items to purchase on an e-commerce store, places to visit, etc. This paper presents A literature survey on different techniques based Recommendation systems. This survey paper explains benefits, their use-cases, and metrics used to compare various algorithms have been discussed. In addition to giving a thorough overview of recommendation systems, this study sheds light on a variety of technologies and trends in the service industry, where recommendation systems are used, for the benefit of several academics who are interested in recommendation systems.